mRNAs biotinylated within the 5′ cap and protected against decapping: new tools to capture RNA-protein complexes - Bednarek, Sylwia; Madan Renes, Vanesa; Bartenschlager, Ralf (Philosophical transactions. Series B, Biological sciences, 2018)
The 5′-terminus of eukaryotic mRNAs comprises a 7-methylguanosine cap linked to the first transcribed nucleotide via a 5′-5′ triphosphate bond. This cap structure facilitates numerous interactions with molecules participating in mRNA processing, turnover and RNA translation. Here, we report the synthesis and biochemical properties of a set of biotin-labelled cap analogues modified within the triphosphate bridge and increasing mRNA stability while retaining biological activity. Successful co-transcriptional incorporation of the cap analogues allowed for the quantification of cap-dependent translation efficiency, capping efficiency and the susceptibility to decapping by Dcp2. The utility of such cap-biotinylated RNAs as molecular tool was demonstrated by ultraviolet-cross-linking and affinity capture of protein-RNA complexes. In conclusion, RNAs labelled with biotin via the 5′ cap structure can be applied to a variety of biological experiments based on biotin-avidin interaction or by means of biotin-specific antibodies, including protein affinity purification, pull-down assays, in vivo visualization, cellular delivery and many others.This article is part of the theme issue ‘5′ and 3′ modifications controlling RNA degradation’.
Gesehen am 10.03.2020